ESTUDO CONTRASTIVO ENTRE CONCEITOS DE GÊNERO E GRAU: É Flexão ou Derivação? CONTRASTING STUDY BETWEEN GENDER AND DEGREE CONCEPTS: Is Flexion or Derivation? - Pessoa, Carine Ribeiro; Botelho, Patricia Ferreira (Episteme Transversalis, 2018)
O presente artigo tem como objetivo discutir os conceitos de gênero e grau tomando, como ponto de partida, a perspectiva tradicional das gramáticas para o estudo da estrutura e formação de palavras em língua portuguesa nas escolas. Ainda não se esgota a possibilidade de discussão desse tema a fim de fundamentar a discussão acerca do processo de flexão e derivação e, para embasar as discussões, teremos como referência os estudos de Gonçalves (2005) e Seabra (2006). Para tanto, será feito um estudo bibliográfico acerca do tema, seguido pela análise de materiais didáticos largamente empregados no Ensino Médio. Abstract The aim of this article is to discuss the concepts of gender and grade, taking as a starting point the traditional perspective of grammar for the study of the structure and formation of words in Portuguese language in schools. It is not yet possible to discuss this topic in order to base the discussion on the process of bending and derivation, and to base the discussions, we will have as reference the studies of Gonçalves (2005) and Seabra (2006). To do so, a bibliographic study about the subject will be done, followed by the analysis of didactic materials widely used in High School.